2008
DOI: 10.1021/jm800612u
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Design of N-Phenyl Tertiary Amines as Transrepression-Selective Liver X Receptor Modulators with Anti-Inflammatory Activity

Abstract: A cocrystal structure of T1317 (3) bound to hLXRbeta was utilized in the design of a series of substituted N-phenyl tertiary amines. Profiling in binding and functional assays led to the identification of LXR modulator GSK9772 ( 20) as a high-affinity LXRbeta ligand (IC 50 = 30 nM) that shows separation of anti-inflammatory and lipogenic activities in human macrophage and liver cell lines, respectively. A cocrystal structure of the structurally related analog 19 bound to LXRbeta reveals regions within the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…It has been shown that different LXR ligands exhibit subtle but distinct differences in the recruitment of coactivators and corepressors required for transcriptional control of gene expression (29). Therefore, it may be possible to identify LXR ligands that only transrepress inflammatory genes, without the transactivation activity (30). LXR modulators with these properties are expected to have less liability associated with LXR transactivation activity such as triglyceride synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that different LXR ligands exhibit subtle but distinct differences in the recruitment of coactivators and corepressors required for transcriptional control of gene expression (29). Therefore, it may be possible to identify LXR ligands that only transrepress inflammatory genes, without the transactivation activity (30). LXR modulators with these properties are expected to have less liability associated with LXR transactivation activity such as triglyceride synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other older generation LXR agonists, it causes increased expression of lipogenic genes including Fas and SREBP1c. A crystal structure of T0901317 bound to hLXRb was thus used to design a series of substituted N-phenyl tertiary amines, which led to the identification of the lead LXR ligand 1,1,3,3,hexafluoro-2-hydroxypropan-2-yl)anilino]methyl]-2,6-dichlorophenol] through profiling in binding and functional assays (Chao et al, 2008). Nuclear receptor selectivity and functional assays showed that GSK-9772 was 100-fold more selective to LXR than either AR, GR, PR, MR, ERa/b, farnesoid X receptor, or PPARa/g/d with little cross-reactivity to PXR (EC 50 = 250 nM).…”
Section: Selective Liver X Receptor Modulatorsmentioning
confidence: 99%
“…This resulted in a greater than 10-fold selectivity for transrepression versus transactivation. Cofactor profiling also revealed key differences between first-generation LXR agonist T1317 and GSK-9772 by the use of mammalian two-hybrid profiling assays with more than 60 amino acid fragments of SRC1 and NCoR, indicative of LXR stabilization in a basal, repressed state by GSK-9772 (Chao et al, 2008). The LXR ligand GSK-9772 thus serves as a valuable chemical tool for exploring nuclear receptor transrepression and will provide an opportunity for the future discovery of selective LXR modulators with improved therapeutic indexes.…”
Section: Selective Liver X Receptor Modulatorsmentioning
confidence: 99%
“…They have been used as therapeutic agents, such as analgesic, antipyretic, anti-inflammatory (Brogden, 1986;Gursoy et al, 2000;Ratnadeep et al, 2010;El-Hawash et al, 2006;Chao et al, 2008), antioxidant (Manojkumar et al, 2009;Watanabe et al, 1994;Ramana Kumar et al, 2012), antiproliferative (Kim et al, 2005), antibacterial (Al-Haiza et al, 2001;Raman et al, 2004), antifungal activities (Vincent, 1999;Ramaraj et al, 2010) and is useful in the treatment of a variety of disorders caused by Human Immunodeficiency Virus (HIV) (Hadi et al, 2010). Pyrazolone derivatives, such as antipyrine (phenazone), 4-aminopyrine (aminophenazone), metamizol (novalgin), and 4-isopropylpyrine (propyphenazone; PP) are analgesic substances (Himly et al, 2003) and edaravone (3-methyl-1-phenyl-2-pyrazoline-5-one) is found as a drug for brain ischemia, myocardial ischemia, treatment of fatal neurodegenerative diseases and cardiovascular diseases (Tsujita et al, 2004;Higashi et al, 2006;Zhang et al, 2012;Kikuchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%